Vitamin D levels and steroid usage are not associated with disease activity in systemic lupus erythematosus patients - Ibrahim, Izzaidah; Wan Mohamed, Wan Mohd Izani; Kah, Keng Wong; Tuan Ismail, Tuan Salwani; Wan Ghazali, Wan Syamimee (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: Suboptimal vitamin D levels are commonly presented by systemic lupus erythemathosus (SLE) patients. This is likely due to protection measures from sunshine exposure adopted by SLE patients to reduce the likelihood of SLE flares onset. In this study, we investigated the vitamin D level among SLE patients and its association with SLE Disease Activity (SLEDAI) scores and among groups of steroid and non-steroid usage. Methods: We recruited 84 SLE patients who attended the Rheumatology Clinic of Hospital Universiti Sains Malaysia from June 2018 until October 2018. Their clinico-demographic data were retrieved and serum vitamin D immunoassay was conducted to measure the vitamin D levels of each patient Vitamin D levels were categorized as normal (≥75nmol/L), insufficient (50-74 nmol/L) or deficient (<50 nmol/L). Comparison between the clinico-demographic parameters with vitamin D levels were conducted using the Fisher’s exact test (for categorical variables) and unpaired t-test (for continuous variables). Results: The mean vitamin D level among the subjects was 40.79 ± 20.2 nmol/L. Fifty-eight (69%) patients were vitamin D deficient, while 20 (23.8%) patients were vitamin D insufficient, and only 6 (7.1%) patients had sufficient level of vitamin D. Vitamin D status was not significantly associated with SLEDAI score (p=0.185) as well as between steroids and non-steroids groups (p=0.255). Conclusion: Vitamin D deficiency occurred in majority of our SLE patients. SLE disease activities were not associated with the status of vitamin D or steroid usage.